1996
DOI: 10.1097/00006842-199601000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Psychological Effects of Natural Disasters

Abstract: Relationships between self-reported psychological distress (Symptom Checklist) and experience with two earthquakes are presented for a group of male factor workers (N = 772) from Naples, Italy, participating in the 1987 follow-up of the Olivetti Heart Study. Although all were exposed to the 1980 earthquake that racked southern Italy, only men residing in the Naples suburb of Pozzuoli experienced the continuing swarm of earthquakes ("bradyseism") of 1983-1984, allowing for the observation of a "natural experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 14 publications
4
120
0
3
Order By: Relevance
“…Dans diverses études, les adules âgés de 50 ans ou plus ont également mentionné avoir ressenti un sentiment de solitude, de désespoir, une diminution de l'estime de soi, une attitude dépressive ainsi qu'un fort sentiment d'isolement après leur exposition à un désastre (Chung, Werrett, Eastrope, & Farmer, 2004;HelpAge International, 2008; Toyabe, Shioiri, Kuwabara, Endoh, Tanabe (Armenian, Melkonian, & Hovanesian, 1998;Kario & Ohashi, 1997;Matsuoka et al, 2000) et psychologique chez les aînés à la suite de leur exposition à un désastre (Arnberg, Eriksson, Hultman & Lundin, 2011;Bland, O'Leary, Farinaro, Jossa, & Trevisan, 1996;Chen et al, 2001;Knight et al, 2000 ;Priebe, Marchi, Bini, Flego, Costa, Galeazzi, 2011). L'adaptation de ces personnes serait plus difficile après une catastrophe lorsque ces dernières s'isolent, ce qui les prédisposerait à la présence de manifestations dépressives, comparativement aux adultes plus jeunes (Christopher, Noreen, Maxine & Yu-Hsuan, 2006;McNaughton, Smith, Patterson, & Grant, 1990;OMS, 2008).…”
Section: Conséquences Des Catastrophes Sur La Santé Biopsychosociale unclassified
“…Dans diverses études, les adules âgés de 50 ans ou plus ont également mentionné avoir ressenti un sentiment de solitude, de désespoir, une diminution de l'estime de soi, une attitude dépressive ainsi qu'un fort sentiment d'isolement après leur exposition à un désastre (Chung, Werrett, Eastrope, & Farmer, 2004;HelpAge International, 2008; Toyabe, Shioiri, Kuwabara, Endoh, Tanabe (Armenian, Melkonian, & Hovanesian, 1998;Kario & Ohashi, 1997;Matsuoka et al, 2000) et psychologique chez les aînés à la suite de leur exposition à un désastre (Arnberg, Eriksson, Hultman & Lundin, 2011;Bland, O'Leary, Farinaro, Jossa, & Trevisan, 1996;Chen et al, 2001;Knight et al, 2000 ;Priebe, Marchi, Bini, Flego, Costa, Galeazzi, 2011). L'adaptation de ces personnes serait plus difficile après une catastrophe lorsque ces dernières s'isolent, ce qui les prédisposerait à la présence de manifestations dépressives, comparativement aux adultes plus jeunes (Christopher, Noreen, Maxine & Yu-Hsuan, 2006;McNaughton, Smith, Patterson, & Grant, 1990;OMS, 2008).…”
Section: Conséquences Des Catastrophes Sur La Santé Biopsychosociale unclassified
“…These findings also seem to hold true for disasters generally [5,12,28]. Indicators include the number of casualties, deaths, losses and disease.…”
Section: Factors Affecting the Development Of Mental Health Disordermentioning
confidence: 71%
“…In the literature, the long-term effects of an earthquake have been studied less extensively. After the 1989 Newcastle earthquake, 48% of the survivors who had PTSD at 6 months after the disaster, still had PTSD at the 2-year post earthquake assessment (16). The study showed that psychological morbidity declined over time but tended to stabilize at about 12 months after a disaster like an earthquake for general morbidity and at about 18 months for trauma-related morbidity (17).…”
mentioning
confidence: 85%